Improved esthetic efficacy and reduced cytotoxicity are achieved with a violet LED irradiation of manganese oxide-enriched bleaching gels - Dias, Marlon Ferreira [UNESP]; Martins, Beatriz Voss [UNESP]; de Oliveira Ribeiro, Rafael Antonio [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2023)
Gels with high concentrations of hydrogen peroxide (H2O2) have been associated with cytotoxicity and consequent post-bleaching tooth sensitivity. This study assessed the bleaching efficacy (BE) and cytotoxicity (CT) of bleaching gels with low concentrations of H2O2 containing manganese oxide (MnO2) and photocatalyzed with violet LED (LEDv). The following groups were established: G1: no treatment (negative control, NC); G2: 35% H2O2 (positive control, PC); G3: LEDv; G4: 10% H2O2; G5: 6% H2O2; G6: 10% H2O2 + MnO2 + LEDv; G7: 6% H2O2 + MnO2 + LEDv. To analyze BE, standardized enamel/dentin discs (E/DDs) were subjected to the bleaching procedures for 45 min (1 session). The color change was determined before and after performing the bleaching protocols (ΔE00; ΔWI). To analyze CT, the E/DDs were adapted to artificial pulp chambers, and the extracts (culture medium + diffused gel components) were applied to cultured odontoblast-like MDPC-23 cells. Then, the cells were assessed concerning their viability (VB), oxidative stress (OxS), and Live/Dead. The amount of H2O2 diffused was also determined (ANOVA/Tukey; p < 0.05). Cell viability decreased in all bleached groups compared to G1 (NC; p < 0.05). The cells in G6 and G7 presented higher viability than in G2, G4, and G5 (p < 0.05). The BE in G7 was similar to G2 (PC; p < 0.05). The lowest OxS and H2O2 diffusion values were found in G6 and G7, compared to the other bleached groups (G2, G4, and G5; p < 0.05). The 6% H2O2 bleaching gel (G7) submitted to both methods of catalysis (MnO2 + LEDv) caused only a mild cytotoxicity and maintained the excellent esthetic outcome promoted by in-office conventional tooth bleaching.
Keywords: Cell culture; Dental materials; Tooth bleaching; Toxicity